Linha Braille: contribuições para maior acessibilidade às informações verbais pelos alunos com surdocegueira - Tino, Cynthia Lanzoni Costa (2018)
Information and Communication Technologies (ICT) are essential tools for serving students with deaf-blindness, given that when included in the pedagogic process, they can contribute favorably to retaining these students in the educational context. New technologies are a reality in the school context, but for the most part, they are underutilized due to a lack of knowledge of, and confidence in the use of these resources among education professionals. Nonetheless, there are many challenges faced by these educators – especially intervening instructors, who are tasked with promoting communications with people with deaf-blindness – in the world in which they are inserted. The adjustments needed, in terms of communication support, should be taken into consideration by educational institutions, given that the lack of these kinds of support create communication barriers, as they deprive students with deaf-blindness from accessing the imparted knowledge and jeopardize the teaching and learning process. The lack of training for special education specialists, such as in the use of refreshable braille displays, hinders the use of this equipment. Thus, the main objective of this study is the proper training of teachers specializing in special education, enabling them to become more confident in the use of refreshable braille displays, by providing the tools and training that will enable them to use the technology in their teaching practice with students with deaf-blindness. The methods used in this study were bibliographic research and field studies with a qualitative approach. The theoretical foundations of this study include: Mec (2010), Nicholas (2011), Baptista (2000), and Kenski (2007). The study subjects were teachers specializing in special education at four different institutions in the South and Central West regions of Brazil. Through the efforts made during the study and the objectives established at the start of the investigation, it was found that these objectives were reached and brought results in the teaching practice, based on a teaching manual created to enable the training of special education specialists, to serve as pedagogical support, giving the teachers more confidence in using the refreshable braille display in their school environment.